African Buffalo Optimization Algorithm for Collision-Avoidance in Electric Fish - Odili, Julius Beneoluchi; Noraziah, Ahmad; Mohd Helmy, Abd Wahab (Taylor & Francis, 2020)
This paper presents the African Buffalo Optimization algorithm for collision avoidance among electric fishes. Collision-avoidance in electric fish finds correlation with the Travelling Salesman avoiding the cities he has earlier visited. Collision avoidance in electric is akin to collision-avoidance in modern day driverless cars being promoted by Google Incorporation and other similar companies. The concept of collision-avoidance is also very useful to persons with visual impairment as it will help them avoid collision with objects, vehicles, persons, especially other visually-impaired. After a number of experimental procedures using the concept of the travelling salesman’s problem to simulate collision-avoidance in electric fish, this study concludes that the African Buffalo Optimization is a veritable tool for simulating collision avoidance in electric fishes.